The Impact of Fintech Technology on Traditional Banking Industry - Hardiyanti, Siti Epa; Thota, Abraham (PT Larva Wijaya Penerbit, 2024)
The rapid evolution of fintech technology has significantly disrupted the traditional banking industry, posing both challenges and opportunities for banks. This study aims to analyze the impact of fintech adoption on the operational and financial performance of traditional banks, focusing on key metrics such as profitability, operational efficiency, and risk. Utilizing a quantitative approach with a descriptive and causal research design, the study collects primary data through surveys and secondary data from financial reports of banks and fintech companies. Panel data regression and ANOVA are employed to assess the relationships between fintech adoption and bank performance. The results indicate that fintech adoption positively influences bank profitability and efficiency, while also introducing new risks that require strategic management. These findings highlight the need for traditional banks to adapt swiftly to remain competitive and secure in an increasingly fintech-driven market. The study contributes to the financial literature by providing empirical evidence on the long-term impacts of fintech on the banking sector, offering valuable insights for both academics and industry practitioners.